Effect of nocturnal melatonin intake on cellular damage and recovery from repeated sprint performance during an intensive training schedule - Farjallah, M. A.; Ghattassi, K.; Ben Mahmoud, L.; Graja, A.; Boudaya, M.; Elleuch, H.; Jammoussi, K.; Sahnoun, Z.; Souissi, N.; Chtourou, H.; Hammouda, O. (Chronobiology International, 2020)
An optimal recovery between training sessions is of similar if not greater importance as the training content and program of the training, itself. One of the most used strategies for improving recovery is the ingestion of supplements. The present study aimed to evaluate the effect of 5 mg oral melatonin supplementation on the recovery from repeated sprint (RSA) of performance and biochemical responses (i.e. oxidative stress, leukocytosis cellular damage) after an intensive training camp (TC). Twenty soccer players performed an RSA test before and after an intensive six-day TC associated with nocturnal melatonin (n = 10) or placebo (n = 10) ingestion. Resting and post-RSA test blood samples were obtained before and after the TC. Compared to placebo, melatonin intake decreased resting oxidative stress markers (i.e, advanced oxidation protein products), leukocytosis (i.e. white blood cells (WBC), neutrophils (NE)) and biomarkers of cellular damage (i.e. creatine kinase (CK)). It also lowered post-exercise leukocytosis (i.e. WBC, NE, lymphocytes (LY), monocytes (MO)) and biomarkers of cellular damage (i.e. CK, aspartate aminotransferase (ASAT), alanine aminotransferase (ALAT)) and raised the activity of the main antioxidant enzymes (i.e. glutathione peroxidase (GPx), glutathione reductase (GR)). In addition, compared to placebo, melatonin reduced the deterioration of the best and total time during the RSA test after the TC. In conclusion, nocturnal melatonin supplementation during an intensive TC alleviated oxidative stress, leukocytosis and cellular damage and improved recovery of RSA performance in soccer players.